BENCANA ALAM DALAM PERSPEKTIF AL-QUR’AN DAN BUDAYA MADURA - Achmad Muhlis (Karsa: Journal of Social and Islamic Culture)
Abstrac:Natural disasters occurring in this country always effect a deep grief to the people. Despite the fact that a number of rhetoric have been  reconstructed to overcome the disaster  from new order up to reformation order. Unfortunately, this is not supported by a concrete action. The questions are that weather the disaster is  either an admonition or a punishment given by Allah?  Why Allah rebukes this country so terribly. This short paper is about to disclose the  meaning behind the disaster from the view point of al-Qur’anKeyword:bencana alam, murka Allah, tolak bala’